Everett Ferguson's Baptism in the Early Church: A Liturgical Appraisal - Senn, Frank C. (Journal of early Christian studies, 2012)
This essay analyzes Everett Ferguson's massive study of Baptism in the Early Church using questions from the catechetical tradition: what is baptism? what are its benefits? how can water do such great things? what is the significance of such a bathing? why does the church baptize infants? These questions get at the phenomenological, theological, ritual, liturgical, and pastoral issues in baptism. I consider baptism to be an extended ritual process of initiation rather than as a discrete ritual act. I question Ferguson's view about submersion in ancient baptismal practice and offer a wider view of the ancient church's practice of infant baptism.